Współczesne poglądy na opiekę menopauzalną - Pertyński, Tomasz; Stachowiak, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2010)
Menopausal period – characterized by many ailments and diseases deteriorating women’s quality of life – needs interdisciplinary health care. Prevention, early detection and proper cure are the basis of so-called menopausal care. Gynecologists with their estrogen-progestin hormonal therapy play still a crucial role in it.